2022
DOI: 10.1108/reps-11-2020-0174
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of unemployment intensity in sub-Saharan Africa: do government intervention and natural resources matter?

Abstract: PurposeAfrican countries are endowed with both human and natural resources. These resources constitute integral components for any economic development due to the long-lasting relationship with all sectors in an economy, yet there is an obvious disagreement between growing economy and employment generation in Africa. Though there has been a growing pattern of economic size, particularly the gross domestic product (GDP) among African countries, most of these economies are low in human development. The disagreem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 78 publications
0
0
0
Order By: Relevance
“…Another issue regarding education systems in SSA is the mismatch between education curricula and job markets [30,31]. This is even more important in the context of high unemployment rates and its interconnections with human development [32] and economic growth [33] This chapter seeks to understand the opportunities and challenges SSA countries are facing compared to what is called the "Asian miracle" in Thailand and Asian Tigers which reaped DD in the early 1960s to the 1990s [34,35]. There are certainly many paths that can be explored to further our understanding of the "Asian miracle."…”
Section: The Ongoing Debate On the Demographic Dividendmentioning
confidence: 99%
“…Another issue regarding education systems in SSA is the mismatch between education curricula and job markets [30,31]. This is even more important in the context of high unemployment rates and its interconnections with human development [32] and economic growth [33] This chapter seeks to understand the opportunities and challenges SSA countries are facing compared to what is called the "Asian miracle" in Thailand and Asian Tigers which reaped DD in the early 1960s to the 1990s [34,35]. There are certainly many paths that can be explored to further our understanding of the "Asian miracle."…”
Section: The Ongoing Debate On the Demographic Dividendmentioning
confidence: 99%
“…Indeed, the contribution of finance on the business performance of small businesses in the world remained significant and imperative. Akinyele, Oloba and Mah (2022) revealed that the single output-multiple inputs framework indicates that on average, there is a low level of government efficiency towards increasing the objective of human development in Africa and as such accentuates infrastructure bottleneck that will enhance growth of MSMEs. Alnaa and Ahiakpor (2015) through survey data attempted to evaluate the strategy which microfinance can employ to increase output among poor micro-entrepreneurs in the Upper East Region of Ghana.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is acknowledged in virtually every nation of the world that MSMEs are indispensable for sustainable economic development regardless of the economic system being adopted and the level of development attained by such an economy (Sanusi, 2013). Micro, Small and Medium Enterprises is of particular relevance in developing economies like Nigeria, because of its potential and catalytic role of increasing employment generation, expanding output, ensuring the development of indigenous technology, promoting entrepreneurial development and ultimately leading to the growth of Gross Domestic Product (GDP) which is a measure of how well an economy is performing (Okun, 1962;Lee, 2000;Viren, 2001;Akinyele, Oloba and Mah, 2022) though there are some views that found otherwise emphasizing that growth may not bring a performance of labour market outcomes (Keller and Nabil, 2002;Akinyele, Oloba and Mah, 2022). In realization of the significance of MSMEs and the problems confronting their performance, a great number of policy actions have been initiated by successive governments in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Sub-Saharan African economies are associated with low per capita income (Gardner, 2022;Gil-Alana et al, 2021;Selassie and Hakobyan , 2021;The World Bank, 2022), high rates of income poverty (Saidi et al, 2023;Schoch and Lakner, 2020), increasing rate of unemployment (Akinyele et al, 2022;Byaro et al, 2023), relatively weak government health expenditure (Eze et al, 2022;Micah et al, 2019), along with poor health outcomes like an increase in infant and maternal deaths, cases of child malnutrition, a shortened life expectancy, and policy mistakes, especially in important economic sectors like the health sector (World Bank, 2013a;2013b;. Dover and Belon (2019) noted that inequalities in health are socially driven leading to a restriction of the poorer population from rising progressively to the desire health state in society.…”
Section: Background Informationmentioning
confidence: 99%